Physics of atmosphere - Houghton, John T. (Cambridge, Cambridge University Press, 1977)
This third edition of John Houghton's acclaimed textbook has been brought completely up-to-date, with several new chapters. Like the previous editions, this is an essential textbook for advanced undergraduate and graduate courses in atmospheric science.
Keywords: Atmosphere